2020
DOI: 10.1111/cdoe.12565
|View full text |Cite
|
Sign up to set email alerts
|

Perceived discrimination in health services and preventive dental attendance in Brazilian adults

Abstract: Objectives It is evident that discriminatory attitudes affect different dimensions of personal life, including health. This study aimed to verify the association between perceived discrimination in health services and preventive dental attendance in Brazilian adults. Methods This cross‐sectional study used secondary data from the 2013 National Health Survey (PNS), a representative survey of the Brazilian population. The response rate was 91.9%, with 60,202 adults agreeing to complete the oral health self‐perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 35 publications
0
20
0
2
Order By: Relevance
“…Thus, unequal relationships between social groups shape their distribution to adverse exposures and health conditions. Discrimination in oral health services in Brazil has been highlighted in a recent study 32 and racism has also affected the dentists' decision concerning the replacement of amalgam restorations 33,34 , emphasizing the structural racism that stereotypes and stigmatizes these populations 10 . In this way, it is important to deeply discuss the social-historical roots of Brazilian racism.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, unequal relationships between social groups shape their distribution to adverse exposures and health conditions. Discrimination in oral health services in Brazil has been highlighted in a recent study 32 and racism has also affected the dentists' decision concerning the replacement of amalgam restorations 33,34 , emphasizing the structural racism that stereotypes and stigmatizes these populations 10 . In this way, it is important to deeply discuss the social-historical roots of Brazilian racism.…”
Section: Discussionmentioning
confidence: 99%
“…One emerging explanation for this association is interpersonal discrimination; however, scholarly work linking discriminatory experiences with oral health is still scant and fragmented. Based on previous reviews 16,25 we identified the publications summarized in Table 1 10,26–45 . All studies have addressed interpersonal discrimination, and only one study tested specific hypotheses based on an intersectional perspective.…”
Section: Existing Research Exploring Oppression and Oral Health Inequ...mentioning
confidence: 99%
“…Based on previous reviews 16,25 we identified the publications summarized in Table 1. 10,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] All studies have We argue, then, that the persistence of oral health inequities over time and across space has much to do with how we employ these categories in our scientific, clinical and policy endeavours. 30,46 Understanding oppression in its structural forms requires attention to how the social, political, commercial/corporate and behavioural determinants intersect and impact oral health outcomes.…”
Section: E Xis Ting Re S E Arch E Xploring Oppre Ss I On and Or Al He...mentioning
confidence: 99%
“…Existing evidence also points to prevailing healthcare inequities. Black Brazilians are less likely to have visited the health services recently, have lower health insurance coverage, and are more likely to be mistreated by a health professional [24][25][26][27][28] . Moreover, Black Brazilians are largely concentrated in Northern and Northeastern regions of the country, which are notoriously known for their lower levels of healthcare availability 29 .…”
Section: Racial Inequities In Brazilmentioning
confidence: 99%